COMPARATIVE STUDY OF VIRECANA KARMA WITH AND WITHOUT MATRA VASTI IN MANAGING STAGE I ESSENTIAL HYPERTENSION (International Journal of Food and Nutritional Sciences, 2022)
Hypertension, characterized by elevated blood pressure levels, poses a substantial global health challenge. Ayurveda offers therapeutic interventions such as Virechana Karma, Urovasti, and Matravasti for its management. This comparative clinical study aimed to assess the effectiveness of these interventions in treating Stage I essential hypertension with Ucca Raktacapa. Sixty participants were randomly assigned to two groups: Group A received Virechana Karma followed by Urovasti, and Group B received Virechana Karma followed by Urovasti and Matravasti. The primary outcome measure was the reduction in systolic and diastolic blood pressure levels. Secondary outcomes included changes in lipid profile, quality of life, and adverse events. Both groups showed significant reductions in blood pressure levels, with Group B demonstrating a greater reduction compared to Group A. These results indicate that the combination of Virechana Karma, Urovasti, and Matravasti shows promise as an effective therapeutic approach for managing Stage I essential hypertension.